Effective School Indicators for Quality Curriculum Implementation Process - Syomwene , Anne (African Journal of Education,Science and Technology (AJEST), 2018)
This is a concept paper on effective school indicators for quality curriculum implementation process. Curriculum implementation is a rather complex process whose success requires various pre-requisites and conditions. The school is the setting where curriculum implementation takes place with the teachers as the agents, learners as the consumers of the curriculum and the educational managers as the supervisors and leaders. This paper is a discussion of some effective school indicators for quality curriculum implementation. Seven key indicators are discussed in this paper: A clear mission, vision and goals; effective learning environment; availability of physical resources and facilities; adequacy of teachers; continued professional development opportunities; teacher and student motivation and effective supervision and leadership. The paper borrows from various discussions on correlates of effective schools advanced by Lezotte (1991), (1992) and (2001); and Association of Effective Schools (1996) as well as other scholars on quality curriculum implementation process. The paper draws examples from schools in Kenya. The paper informs teachers and other education stakeholders on quality curriculum implementation process.